50.0k views
2 votes
Simplify
99=2(-7b-3)+7​

User Stu Harper
by
6.1k points

2 Answers

4 votes

b = -7 is the answer

User Rohan Patil
by
5.4k points
2 votes

Answer:

b=-7

Explanation:

Simplifying

99 = 2(-7b + -3) + 7

Reorder the terms:

99 = 2(-3 + -7b) + 7

99 = (-3 * 2 + -7b * 2) + 7

99 = (-6 + -14b) + 7

Reorder the terms:

99 = -6 + 7 + -14b

Combine like terms: -6 + 7 = 1

99 = 1 + -14b

Solving

99 = 1 + -14b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '14b' to each side of the equation.

99 + 14b = 1 + -14b + 14b

Combine like terms: -14b + 14b = 0

99 + 14b = 1 + 0

99 + 14b = 1

Add '-99' to each side of the equation.

99 + -99 + 14b = 1 + -99

Combine like terms: 99 + -99 = 0

0 + 14b = 1 + -99

14b = 1 + -99

Combine like terms: 1 + -99 = -98

14b = -98

Divide each side by '14'.

b = -7

Simplifying

b = -7

User Piyush N
by
5.7k points